Efek Media Zoom Cloud Meeting Terhadap Keaktifan dan Hasil Belajar Bahasa Indonesia Siswa di Masa Pandemi Covid-19 - Sri Rahayu B; Sulastriningsih Djumingin; Munirah Munirah (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
This study aims to analyze the effect of the zoom cloud meeting on the activeness and learning outcomes of Indonesian students during the Covid-19 pandemic. The population of this study amounted to 153 students. This study uses descriptive correlation method. The subjects of this study were students of class VIII.1 MTs Negeri Barru in Barru Regency, as many as 25 students. Sampling was done by using simple random sampling. The instrument used is a test in the form of multiple choice questions. The data analysis technique used was descriptive statistical analysis. The analysis carried out is a statistical test. The tests carried out consisted of the Shapiro-wilk normality test, and hypothesis testing with simple regression analysis. The results of this study indicate (1) The results of students' Indonesian learning before applying the zoom cloud meeting media have not been maximized, indicating that the average value obtained is 59.64%. (2) The effect of the zoom cloud meeting media greatly helps students in activeness and learning outcomes of Indonesian shows that the average value obtained is 80.04%. (3) After implementing the zoom cloud meeting media on the activities and results of learning Indonesian students during the Covid-19 pandemic and before applying the zoom cloud meeting media there was an effect on the process and results shown by the students.